Comparison of Retaining Walls from Half-Panel Interlocking Bricks with Dry Joints Reinforced with GFRP Material and Stud Steel - Bubpi, Attaphol; Amornpinyo, Prach; Teerawong, Jaruek (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
This research aimed to compare a half-panel interlocking brick retaining wall model reinforced with GFRP material against one reinforced with steel stud. To study the behavior of horizontal movement of the retaining walls, a model with the size of 1.60 meter height and 2.00 meter width was reinforced with GFRP material and steel stud of compressive strength of 10, 20, and 30 lbs. Lateral soil pressure was applied and it transmitted the settlement of sand in the steel model after which its horizontal displacement was considered. The test results of the half-panel interlocking bricks with dry junction reinforced with GFRP material had the highest horizontal displacement values of 4.87, 3.82, and 3.25 millimeters, respectively, and showed higher values than those of steel stud reinforced samples by 4.74, 5.40, and 7.05 millimeter, respectively. The GFRP reinforced material showed less horizontal movement compared to those of reinforced with steel stud by 30.92, 29.26, and 31.33 %, respectively.